Experiences with Continuous Positive Airway Pressure Among African American Patients and their Bed Partners. Issue 3 (4th May 2023) - Berg, Kristen A.; Marbury, Marquisha; Whaley, Morgan A.; Perzynski, Adam T.; Patel, Sanjay R.; Thornton, J. Daryl
ABSTRACT: Rationale: Despite having a higher prevalence and severity of obstructive sleep apnea (OSA), African Americans have lower adherence to continuous positive airway pressure (CPAP) compared to other groups. Information regarding challenges faced by African Americans prescribed CPAP are lacking. Objectives: To determine the barriers and facilitators to optimal management of OSA with CPAP among African Americans and to understand the role bed partners may play. Methods: We conducted semi-structured in-depth interviews via video conferencing with African American patients of an urban safety-net health care system with OSA prescribed CPAP and their bed partners. Recruitment continued until theoretical saturation was achieved. Verbatim transcripts were analyzed using the principles of thematic analysis. Results: 15 patients (12 women) diagnosed with OSA and prescribed CPAP a mean 2.6 years prior along with 15 bed partners (3 women) were individually interviewed. Four themes emerged regarding impediments to CPAP use: 1) inadequate education and support, 2) CPAP maintenance and hygiene, 3) inconvenient design of CPAP interfaces, and 4) impediment to intimacy. Four themes emerged as facilitators to CPAP use: 1) provider and technical support, 2) properly fitted CPAP masks, 3) active support from partner and family, and 4) experiencing positive results from CPAP. Conclusions: African American patients with OSA and their bed partners identified several unique barriers and facilitators to CPAP use. Active involvement by bed partners was considered by both patients and partners as helpful in improving CPAP adherence. Interventions to improve OSA outcomes in this population should focus on patients and their bed partners.